President's Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2016)
Pillar Chair for the National Conference Planning committee, Kim McLennan-Robbins, and myself recently conducted a site visit to Niagara Falls, ON, in preparation for the ORNAC National Conference, Harnessing our Power, taking place April 30 to May 4, 2017. When we arrived I was struck by the magnificent beauty and power of the falls. I found the area to be exciting and uplifting and I think it is a very fitting place to bring perioperative registered nurses and associates together for this inspirational and empowering event.